Occupational stress and its relationship with need le stick injury among emergency department personnel - A Sharifian; O Aminian; L Afshari Saleh (طب کار)
Introduction: Emergency personnel are usually exposed to needle stick injuries (NSI) and contamination with HBV, HCV & HIV. The cost of health and psychological effects of such injuries demonstrates the importance of evaluating its risk factors and preventing it. One of these factors is job stress. Methods: A cross-sectional study was conducted among emergency personnel of 4 university hospitals in Tehran in 2008 - 2009. A triplex questionnaire was used including demographic features, Nordique psychological stress questionnaire and SPSS (Ver. 11) was used for analysis of the data. Results: Tree hundred and fifty respondents including 162 (46.3%) males and 188 (53.7%) women, with an average age of 30±5.6 years including 146 residents (41.7%),43 interns (12.3%) & 161 nurses (46%) entered the study. Sixty nine persons (19.7%) reported a history of NSI and 99 persons (28.3%) had Blood and Body fluid exposure during last 3 months.158 persons (45.1%) were classified as low, 158 (45.1%) as moderate and 34 (9.8%) as severe stress level. there was not any significant difference between the proportion of NSI in different stress levels (P=0.374), but there was a significant difference in NSI proportion between nurses, and interns, residents (P=0.002). Conclusion: This study demonstrates that the frequency of NSI & BBFE in emergency personnel is significant, especially in residents. So it’s necessary to have a program for reducing it. The stress level didn't influence the rate of NSI. We suggest doing a survey to study the relationship between NSI and job stress factors (such as workload, role ambiguity) separately.